Przybyli do getta ... odeszli w nieznane ... zagłada Żydów w Generalnym Gubernatorstwie : katalog wystawy : the extermination of Jews in the General Government : exhibition catalogue = They arrived at the ghetto ... and went into the unknown .. - Kuwałek, Robert 1966-2014; Libionka, Dariusz 1963-; Państwowe Muzeum na Majdanku (Państwowe Muzeum na Majdanku, 2013)
Includes bibliographical references